An Analysis of Abstract and Practical Knowledge about Climate Change (Case Study: Students of Mazandaran State Universities) - Sadegh Salehi; Karim Soleymani; Zahra Pazokinejad (نشریه جغرافیا و برنامه‌ریزی, 2016)
The purpose of this study is to examine students' theoretical and applied knowledge of climate change and social factors influencing it. To conduct the research, descriptive-analytical method was used and 187 students of Mazandaran state universities were selected by stratified sampling. The questionnaire was applied to collect data then data was analyzed using SPSS statistical software. Results of the study showed that the level of students’ abstract and practical knowledge of climate change is high and there is relationship between environmental information sources, perceived performance and students' knowledge of climate change. The results showed no significant difference between level of knowledge and gender and place of residence of the surveyed students and students’ knowledge of climate change is different to college. Overall, the results indicate that there is a requirement of environmental education and this suggests that the subject matter of climate change and policies should be included in curriculum of all university courses.